First Experience with the New MitraClip NTR/XTR Device. Issue 4 (4th July 2019) - Möllmann, Helge; Bayer, Matthias; Blumenstein, Johannes; Dörr, Oliver; Marks, Maritta; Dyckmanns, Nils; Dohmen, Guido; Sydow, Michael; Al-Terki, Hani; Husser, Oliver; Hamm, Christian W.; Nef, Holger; et al.
ABSTRACT: Background: Percutaneous mitral valve repair using the MitraClip system is a well-established method for a subset of patients with severe mitral regurgitation (MR) at high risk for surgery. Two new versions of the device are now available with different clip sizes and changes regarding the shaft. We examined the handling of the new MitraClip XTR/NTR systems and report the first clinical outcomes using these devices in a multicenter registry. Methods: We treated a total of 23 consecutive patients between March and May 2018: 11 with functional MR (FMR), 7 with degenerative MR (DMR), and 5 with combined FMR/DMR. In all procedures, the XTR was used as the first clip. In ninepatients a second clip was implanted (XTR in six and NTR in three). Results: Procedural success was achieved in 100%. MR was reduced significantly in all cases, resulting in 21 cases with mild or low MR and two cases with low to moderate MR. The v-wave was reduced from 29 ± 9 mmHg to 17 ± 7 mmHg (mean±SD; p < .001). Advantages of the new system are the ability to treat pathologies with large gaps and to perform the procedure after a high transseptal puncture. Easier grasping with the XTR resulted in a fast (procedure time 47 ± 15 min (mean±SD)), successful positioning of the clip with the first grasp in most (56.5%) cases. Conclusion: Changes in the MitraClip device permit a faster procedure with good results in severe pathologies. With two clip sizes the procedure can be individualized with respect to patient anatomy.